STATEMENT OF MECHANICAL PROPERTIES OF MATERIALS WHICH HAVE ANALYZED - Istiyono, Edi (Jurnal Penelitian Saintek, 2006)
The experiment purposes to observe 0(’ (1) the influence of temperature to the [ensile strength of material. (2) the influence of anneal lime to the tensile strength of material. (3) the influence (if temperature to the torsion modulus (if material, (4) the irfluence (if anneal lime to the torsion modulus of material. and (5j discover the material that has optimum of tensile strength and torsion modulus. Sample of the experiment is win! of ion. steel and copper which are annealed 011 temperature of 15()°C, 25)°C, 350°C, 45()"C, 550"C, 650"C. 750°C. 850°C, and 950°Cfor 30 minutes. Besides. the wires are annealed on temperature 350°Cfor 30.60, 9().120. 150. IBO. ]J() and 240 minutes. The tensile strength of materials is measured with a tensometer. Tension modulus of materials is measured with tension modulus meter. Based on data analysis is concluded thai. ( l ) Increasing of the temperature anneal causes decreasing of ttle tensile strength of the materials. (2) increasing of the time anneal causes decreasing of the tensile strength (if the materials. (3) increasing (if the temperature anneal causes decreasing of the torsion modulus of the materials. (-/) increasing of the anneal time causes decreasing of the torsion modulus of the materials. and (5) the optimum tensile strength is the steel which anneal temperature of 450°C and anneal time (if 30 minutes. The optimum torsion modulus is iron, which is not annealed.